2013
DOI: 10.1016/j.juro.2013.03.076
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity and Self-Reported Compliance with American Urological Association Best Practice Recommendations for Use of Thromboembolic Prophylaxis among American Urological Association Members

Abstract: Although younger age and self-reported urological oncologist and/or laparoscopic/robotic specialist status correlated strongly with thromboprophylaxis use, self-reported adherence to AUA Best Practice Statement was low, even in high risk cases with clear AUA Best Practice Statement recommendations such as radical cystectomy. These data identify opportunities for quality improvement in patients undergoing major urological surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 26 publications
1
24
2
Order By: Relevance
“…A second survey that polled practising AUA members also showed low rates of thromboprophylaxis use for major pelvic urological surgery [5]. Of the respondents to this survey, only 71% would frequently or always prescribe prophylaxis, while 19% would never or infrequently prescribe prophylaxis for patients undergoing cystectomy who were at high risk of VTE; the percentages for prescribing prophylaxis decreased to 61 and 28%, respectively, for a low-risk patient.…”
Section: Variations In the Use Of Venous Thromboembolism Prophylaxis mentioning
confidence: 87%
See 2 more Smart Citations
“…A second survey that polled practising AUA members also showed low rates of thromboprophylaxis use for major pelvic urological surgery [5]. Of the respondents to this survey, only 71% would frequently or always prescribe prophylaxis, while 19% would never or infrequently prescribe prophylaxis for patients undergoing cystectomy who were at high risk of VTE; the percentages for prescribing prophylaxis decreased to 61 and 28%, respectively, for a low-risk patient.…”
Section: Variations In the Use Of Venous Thromboembolism Prophylaxis mentioning
confidence: 87%
“…When comparing the thromboprophylaxis guidelines a spectrum of recommendations appear (Table 3). This divergence of recommendations contributes significantly to the heterogeneity of practice among urologists [4][5][6].…”
Section: Trade-off Of Bleeding and Venous Thromboembolism Risk For Pamentioning
confidence: 99%
See 1 more Smart Citation
“…The American Urological Association (AUA) has issued its own best practice statement regarding the use of thromboprophylaxis in patients undergoing urologic surgery 22 ; however, it makes no recommendations with respect to extended-duration prophylaxis. 23 Bergqvist et al conducted a double-blinded randomized controlled trial to assess the efficacy of extended-vs shortduration enoxaparin prophylaxis among patients undergoing open abdominal or pelvic surgeries for malignancy. The trial demonstrated benefit to extended-duration prophylaxis with respect to VTE incidence without an associated increase in hemorrhagic complications; however, patients undergoing surgery for cancers of the genitourinary tract composed <10% of the study population.…”
Section: Commentmentioning
confidence: 99%
“…This is lower than the rate of recently published mail surveys but congruent with the rate of recently published electronic surveys. 12,15 Electronic surveys may be a limitation to survey based studies, given the lower response rate. The response rate of future survey based studies may improve with electronic and mail correspondence.…”
Section: Discussionmentioning
confidence: 99%